2004
DOI: 10.1111/j.1447-0594.2004.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognosis and satisfaction after percutaneous endoscopic gastrostomy in a general hospital*

Abstract: Background: Percutaneous endoscopic gastrostomy (PEG) has been widely acknowledged as a safer method for enteral feeding; however, its long-term impact on prognosis and quality of life in elderly patients is not sufficiently understood. There are issues still to be studied regarding the indications for PEG, due to the lack of convincing evidence that it reduces expected complications such as aspiration pneumonia or for improving the prognosis of patients with severe dementia. Method:In this study we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Rejecting tube feeding in approximately 90% of the families caring for these terminal patients might decrease tube feeding by half 3 . Onishi et al 18 . reported that approximately half of families were satisfied with gastrostomy tube feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rejecting tube feeding in approximately 90% of the families caring for these terminal patients might decrease tube feeding by half 3 . Onishi et al 18 . reported that approximately half of families were satisfied with gastrostomy tube feeding.…”
Section: Discussionmentioning
confidence: 99%
“…17 Rejecting tube feeding in approximately 90% of the families caring for these terminal patients might decrease tube feeding by half. 3 Onishi et al 18 reported that approximately half of families were satisfied with gastrostomy tube feeding. The quality of informed consent for placement of the gastrostomy tube was inadequate in a large community-teaching hospital.…”
Section: Figurementioning
confidence: 99%
“…In addition, low lymphocyte count was a risk factor for patients treated with PEG for malignant diseases. Previous studies did not evaluate long-term survival, but have indicated that the prognosis of PEG is influenced by several factors, including aging, sex, dementia, low serum albumin level, low serum cholesterol level, hyponatremia, and severe comorbidity including complicated pneumonia, cardiovascular diseases, and malignant diseases (2)(3)(4)(6)(7)(8)(9)(10)(11)(12). Judging from the one-year follow-up in the present study, nutritional status, as reflected by serum albumin level, might be crucial for survival after PEG, although rapid turnover proteins and other markers of nutritional status were not evaluated in the present retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Although placement of a PEG tube is aimed for long‐term rather than short‐term enteral nutrition in most cases, the prognosis varies considerably between cases. Many factors seem to be associated with a long‐term prognosis complicatedly, but few studies have evaluated long‐term outcomes and prognostic factors related to PEG in Japan 3,4 . Therefore, we investigated long‐term survival and prognostic factors in patients who underwent this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors seem to be associated with a long-term prognosis complicatedly, but few studies have evaluated long-term outcomes and prognostic factors related to PEG in Japan. 3,4 Therefore, we investigated long-term survival and prognostic factors in patients who underwent this procedure.…”
Section: Introductionmentioning
confidence: 99%